2019
DOI: 10.4110/in.2019.19.e12
|View full text |Cite
|
Sign up to set email alerts
|

The autophagy Protein Atg5 Plays a Crucial Role in the Maintenance and Reconstitution Ability of Hematopoietic Stem Cells

Abstract: Hematopoietic stem cells (HSCs) in bone marrow are pluripotent cells that can constitute the hematopoiesis system through self-renewal and differentiation into immune cells and red blood cells. To ensure a competent hematopoietic system for life, the maintenance of HSCs is tightly regulated. Although autophagy, a self-degradation pathway for cell homeostasis, is essential for hematopoiesis, the role of autophagy key protein Atg5 in HSCs has not been thoroughly investigated. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 36 publications
(39 reference statements)
6
33
0
Order By: Relevance
“…The Atg5 deletion efficiency was sufficiently high using this system (Supplementary Figure S1 ). Consistent with previous reports 29 , 30 , Atg5 f⁄f ; Vav mice showed severe haematopoietic failure at 7 weeks of age, and most Atg5-deficient mice died presumably because of further progression of haematopoietic failure (Supplementary Fig. S2 ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The Atg5 deletion efficiency was sufficiently high using this system (Supplementary Figure S1 ). Consistent with previous reports 29 , 30 , Atg5 f⁄f ; Vav mice showed severe haematopoietic failure at 7 weeks of age, and most Atg5-deficient mice died presumably because of further progression of haematopoietic failure (Supplementary Fig. S2 ).…”
Section: Resultssupporting
confidence: 92%
“…5 c). Consistent with previous reports, granulocyte–macrophage progenitors (GMPs) were reduced significantly 30 , and common myeloid progenitors (CMPs)/megakaryocyte-erythrocyte progenitors (MEPs) were reduced similarly. Additionally, we found that mature B cells in BM were reduced drastically in Atg5 f⁄f ; Vav mice (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Then, alveolar macrophages were finally gated with CD11c hi CD11b int , and eosinophils were gated with CD11c int CD11b hi . The analysis of immune cells was performed according to previously described methods [20].…”
Section: Methodsmentioning
confidence: 99%